GREEN SUSTAINABILITY AND FINANCIAL PERFORMANCE OF HALAL FOOD COMPANIES: EVIDENCE OF MALAYSIA - Rahman, Md Mahfujur; Ahmad, Zaki; Mokal, Mahvish Nawaz; Aziz, Muhamad Fikri; Mhd Khotib, Nor Aina (Bank Indonesia, 2024)
With growing concerns about environmental degradation and its impact on global ecosystems, the Halal food industry is facing increasing scrutiny and pressure to adopt sustainable practices. This research examines the relationship between green sustainability and the financial performance of Halal food companies in Malaysia. Applying a dynamic panel modelling to a sample of 75 companies over 10 years, we document diverse effects of sustainable practices on firms’ financial performance. More specifically, we note that efficient material usage is positively associated with both Return on Assets (ROA) and Tobin's Q (TBQ). Likewise, by reducing costs and enhancing the company's public image, effective emission management boosts both ROA and TBQ. However, energy-related initiatives negatively impact both ROA and TBQ. Biodiversity efforts, although costly in the short term, contribute to improved long-term market valuation. In a similar vein, while its decreases short-term profitability, environmental sustainability positively influences market valuation. Finally, water management initiatives often lead to decreased ROA and TBQ, which possibly is related to their high costs. From the results, policymakers should support efficient material usage and emission management through incentives to enhance profitability and market valuation. Additionally, they should consider providing financial assistance for biodiversity and environmental compliance initiatives while evaluating ways to mitigate the high costs associated with energy and water management to ensure sustainable industry growth. ACKNOWLEDGMENT We extend our sincere gratitude to the Institute of Halal Management, Islamic Business School, University Utara Malaysia, and the Research and Innovation Management Centre (RIMC) for their invaluable support and contribution to our current research. The institutional support from both entities has greatly enriched our study, emphasizing the significance of sustainable practices in the Halal food industry.